Syngnathia: a jaw dropping case of fused jaws in a neonate - Bharadwaj, Shruthi Kumar; Prasad, Prashasti; Kudva, Adarsh; Prabhu, Santosh; Lewis, Leslie Edward (International Journal of Contemporary Pediatrics, 2024)
Syngnathia is an extremely rare condition with a congenital fusion of the maxilla and mandible described as an occlusion of the oral cavity opening. No case of complete bony synostosis, identified in the new-born period have survived beyond few months of age, hence making this case a novel addition to literature. Here we present a case of a term neonate with fused maxillo-mandibular jaws and synechial closure of the mouth with subtle dysmorphic features. Respiratory distress and feeding issues remained the most important challenges. Investigations with baseline radiography, a 3D CT reconstruction of the head, face and neck anatomy elucidated bilateral bony fusion of maxillomandibular jaws, a midline cleft in the soft palate and micro-glossia. After initial stabilisation, surgical intervention was done in two graded phases. First, an orifice was established to enable an airway route, in an anticipation of difficult airway in an event of distress followed by major synechiae and bony excision with placement of an oral distractor and exteriorisation of the small tongue. With multi-disciplinary team effort and physio-motor stimulation, she was established on direct breast feeding by 37 days of life. She was developmentally normal at 7 months of age with decent growth.